THE EFFECT OF PROFITABILITY AND CAPITAL INTENSITY AGAINST TAX VOIDANCE IN MINING SECTOR COMPANIES - Hadli .; Angka Wijaya; Rudi Ananda; Abdullah Rasjid (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
It is quite unexpected that within the tax environment, instances of tax evasion through a few people who are now no longer complying with tax rules to decrease the quantity of tax that groups must pay to be able to obtain better income are still frequent. This observation became performed by the authors to illustrate the consequences of profitability and capital depth variables on tax avoidance of mining zone corporations indexed at the Indonesian Stock Exchange. The first observed population consisted of 34 mining corporations indexed at the Indonesian Stock Exchange from 2014 to 2021. The sampling technique for this observe come 14 corporations indexed the usage of the centered sampling technique and met all pattern choice criteria. The records used in this observation are secondary records inside the shape of economic statements taken from the company's annual report. The F take a look at effects display that each profitability and capital depth have a vast impact on tax avoidance at the identical time, which may affirm the regression version covered in this observation. A partial t take look at indicates that profitability has a bad impact on tax avoidance, whilst capital depth has no vast impact on company tax avoidance.